Morphotropic phase boundary in (1-x)BiFeO3-xPbTiO3: Phase coexistence region and unusually large tetragonality - Bhattacharjee S.; Tripathi S.; Pandey D. (My University, 2025)
It is shown that the tetragonal (T) and rhombohedral (R) structures of (1-x) BiFe O3 -xPbTi O3 are stable for xT 0.31 and xR ≤0.27, respectively, giving the narrowest width of 0.03, reported so far, for the morphotropic phase boundary region in this system. The Rietveld refined structure of the T phase for x=0.31 reveals partial covalent character of the TiFe-O and PbBi-O bonds which may be responsible for the unusually large tetragonality. © 2007 American Institute of Physics.